ISOLATION AND PHENOTYPIC CHARACTERISATION OF MORPHOLOGY IN FUNGUS Beauveria bassiana (Balsamo) Vuillemin COLONY NATURALLY FROM LEAF SURFACE, SOIL, AND INSECT AS HOST IN TOMATO PLANTATION - Affandi, Aminuddin; Chailani, Siti Rasminah; Mimbar, Saubari M.; Wiroatmodjo, Boedijono (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2012)
Virulence of fungus Beauveria bassiana as pathogen on insect can be predicted according to phenotypic character in colony morphology. First of all, isolates of three different habitats were taken. Furthermore, their phenotypic characters was further characterised in B. bassiana colony and the colony growth rate was also monitored. The three natural habitats comprised insects, soil in tomato plantation and the surface of tomato leaves. The result showed that B bassiana isolate managed to be isolated from the three natural habitats involving larva Spodoptera litura and Helicoverpa armigera, the soil, and surface of tomato leaves. B bassiana isolate of insect habitat represented phenotype in colony morphology with curved character, while isolate of the leavesâ surface and soil indicated phenotype in colony morphology with raised and bowl-shaped character. In addition to the colony characters, varied growth rate was also indicated by isolate from each habitat. Isolate of insect with curved colony character represented higher growth rate than that of the leavesâ surface or the soil with raised and bowl-shaped colony character. The colony with curved character represented phenotypic character of isolate B bassiana with high growth rate. Thus, B. bassiana isolate with the curved colony of insect served as an isolate which was expected to be virulent as controlling agent to biological elements. Â Â Â Â Keywords: B. bassiana isolate, phenotypic characters in colony morphology, colony growth rate, habitat of fungus